Numerical study of elastic-plastic behaviour of pore-containing materials: effects of pore arrangement. (4th February 2022) - Shen, Yu-Lin; Fathi, Nima
The present investigation aims to evaluate the elastic and plastic behaviour of porous materials through micromechanical modelling. Nonlinear computational analyses were conducted using the finite element method (FEM). The effective elastic and plastic behaviours of the model structures, encompassing a range of porosity up to 20% with various pore geometries, were investigated. Attention is directed to the uniaxial stress-strain response as a function of the porous microstructure. The model geometries were generated based on non-overlapping pore topologies arranged in an orderly manner. The sensitivity of the results to the pore morphology was examined by comparing the normalised effective modulus of elasticity for all cases, and was validated by the experimental data. As expected, the introduction of porosity was found to reduce the elastic modulus of the media. Also, the pore arrangement variation has a direct influence on the effective mechanical response beyond the elastic limit. In addition, stress distribution in the porous microstructure was significantly influenced by the pore morphology. The approach can be readily generalised to study a wide variety of porous solids from nano-structured materials to geological structures.